Cost-effectiveness and cost–utility of endovascular versus open repair of ruptured abdominal aortic aneurysm in the Amsterdam Acute Aneurysm Trial. Issue 3 (27th January 2014) - Kapma, M R; Dijksman, L M; Reimerink, J J; de Groof, A J; Zeebregts, C J; Wisselink, W; Balm, R; Dijkgraaf, M G W; Vahl, A C
Abstract: Background: Minimally invasive endovascular aneurysm repair (EVAR) could be a surgical technique that improves outcome of patients with ruptured abdominal aortic aneurysm (rAAA). The aim of this study was to analyse the cost-effectiveness and cost–utility of EVAR compared with standard open repair (OR) in the treatment of rAAA, with costs per 30-day and 6-month survivor as outcome parameters. Methods: Resource use was determined from the Amsterdam Acute Aneurysm (AJAX) trial, a multicentre randomized trial comparing EVAR with OR in patients with rAAA. The analysis was performed from a provider perspective. All costs were calculated as if all patients had been treated in the same hospital (Onze Lieve Vrouwe Gasthuis, teaching hospital). Results: A total of 116 patients were randomized. The 30-day mortality rate was 21 per cent after EVAR and 25 per cent for OR: absolute risk reduction (ARR) 4·4 (95 per cent confidence interval (c.i.) –11·0 to 19·7) per cent. At 6 months, the total mortality rate for EVAR was 28 per cent, compared with 31 per cent among those assigned to OR: ARR 2·4 (−14·2 to 19·0) per cent. The mean cost difference between EVAR and OR was €5306 (95 per cent c.i. –1854 to 12 659) at 30 days and €10 189 (−2477 to 24 506) at 6 months. The incremental cost-effectiveness ratio per prevented death was €120 591 at 30 days and €424 542 at 6 months. There was no significant difference in quality of life between EVAR and OR. Nor was EVAR superior regarding cost–utility. Conclusion: EVAR may be more effective for rAAA, but its increased costs mean that it is unaffordable based on current standards of societal willingness-to-pay for health gains. Abstract : Endovascular aneurysm repair not cost-effective